2013
DOI: 10.5301/hip.2013.10718
|View full text |Cite
|
Sign up to set email alerts
|

The Collum Femoris Preserving Stem: Early Results

Abstract: Femoral neck preserving stems have been developed to take advantage of the biomechanical properties of the femoral neck, and to optimise femoral anchorage and load distribution. The aim of this study was to report the clinical and radiological results in a group of 126 patients (150 hips), operated on for a total hip arthroplasty with the CFP stem. Clinical evaluation considered Harris Hip Score (HHS), thigh pain, Charnley classification, peri- and post-operative complications. Radiographic variables were stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…In addition, a comprehensive hip evaluation including ROM and impingement testing should be performed. This allows the practitioner to glean a better understanding of the patient’s specific lumbopelvic mechanics [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a comprehensive hip evaluation including ROM and impingement testing should be performed. This allows the practitioner to glean a better understanding of the patient’s specific lumbopelvic mechanics [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…[3], Pipino F., Nowak M., Ghera S. [4], tỷ lệ còn tồn tại của nhóm khớp này là 99,3% (từ 96,6% đến 100%) với thời gian theo dõi trung bình 6,3 năm (từ 2 -17 năm).…”
Section: Kết Quả Nghiên Cứu Và Bàn Luậnunclassified
“…7 A previous study showed that the CFP stem effectively restores FO and optimizes biomechanical properties. 8 However, another study comparing the CFP stem with the ribbed stem demonstrated that the CFP stem was more likely to cause an increase in the leg length and the occurrence of periprosthetic fractures. 9 Klein et al 10 showed that both the CFP stem and the Corail stem (DePuy Orthopaedics, Warsaw, IN, USA) had similar hip function scores, but they did not evaluate the FO or leg length.…”
Section: Introductionmentioning
confidence: 99%